Description of Parent's Support on Development of Early Reading Skills - Wahyu Rahmadani; Ismaniar Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
This research motivated by the large of children aged 5-6 years who have quite high reading ability in Jorong VII Pasar Lama Lubuk Basung, Agam Regency.This type of research is quantitative descriptive research. The population in this reaseach were parents who had children aged 5-6 years in Jorong VII Pasar Lama Lubuk Basung, Agam Regency, amounting to 35 people. Samples are taken with the intention or purpose of 21 parents. Data analysis techniques use a percentage formula.The results of the reseach: 1) parental support to provide guidance in the form of directing, accompanying, and rectifying can be categorized as good. 2) Furthermore, parents' support to give praise in the form of verbal non-verbal praise can be categorized as good. 3) parental support to provide encouragement in the form of giving gifts and providing facilities can also be categorized as good. Keywords: Support, Development, Reading Beginning